2012
DOI: 10.1039/c2ee21964f
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of CEA microbial fuel cells with increased reactor size

Abstract: The performance of an over 10 times larger microbial fuel cell (MFC) with double cloth electrode assemblies (CEAs) during 63 days of continuous operation demonstrates that the excellent performance of CEA-MFCs can be further improved during scale-up. With a new separator material and U-shaped current collectors, the larger MFC produced a maximum power density of 4.30 W m À2 at a current density of 16.4 A m À2 , corresponding to a volumetric power density of 2.87 kW m À3 at 10.9 kA m À3 for a double CEA-MFC. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(97 citation statements)
references
References 28 publications
4
91
1
1
Order By: Relevance
“…The presence of a certain amount of oxygen in anode chamber was reported to enhance the performance of microbial fuel cells [24,25]. In this work, we isolated functional microbes from micro-aerobic anode chamber to elucidate their electron transfer mechanism.…”
Section: Gram-positive Bacillus Sp Ws-xy1 and Yeast Pichia Stipitismentioning
confidence: 99%
“…The presence of a certain amount of oxygen in anode chamber was reported to enhance the performance of microbial fuel cells [24,25]. In this work, we isolated functional microbes from micro-aerobic anode chamber to elucidate their electron transfer mechanism.…”
Section: Gram-positive Bacillus Sp Ws-xy1 and Yeast Pichia Stipitismentioning
confidence: 99%
“…This makes it hard to realize the energy and economic revenues. Although a maximum volumetric power density of 2.87 kW/m 3 (normalized to the fuel cell volume) has been achieved in a 30 ml MFC with a cloth electrode assembly configuration (Fan et al, 2012), the value decreased substantially (typically to less than 35 W/m 3 ) when the fuel cell size was increased from milliliter-scale to liter-scale (Dekker et al, 2009). It has been suggested that MFCs should have to be able to produce at least 400 W/m 3 to be competitive with traditional anaerobic digestion , and to have an output of 1 kW/m 3 (at an organic loading rate of 10 kg-COD/(m 3 •d)) to achieve energy self-sufficiency (Rabaey and Verstraete, 2005).…”
Section: Mfcs For Sustainable Wastewater Treatment: Opportunities Andmentioning
confidence: 99%
“…From the economic point of view, expensive membranes, such as ion exchange membranes, ultra filtration membranes, and forward osmosis membranes are not suitable for use in large-scale MFCs. A promising low-cost separator material is non-woven cloth (Fan et al, 2012;Wang et al, 2013), but its mechanical strength and long-term stability still need to be improved. The development of low cost, proton transferable, and long-term stable separator materials is very important for large-scale MFCs in the future.…”
Section: Reducing Capital Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma possível fonte de energia renovável a ser empregada é a implementação de célula combustível microbiana (CCM), pois dentre suas aplicações destacamse exemplos relacionados à geração de energia elé-trica a partir do tratamento de águas residuárias ((DU;GU, 2007), (GHANGREKAR;SHINDE, 2007) e (FAN;HAN;LIU, 2012)). Esses sistemas podem ser operados com diferentes substratos, devido a flexibilidade dos micro-organismos que se utilizam destes substratos, de modo a degradá-los para a subsequente geração de eletricidade a partir de resíduos e biomassa ((ZHANG et al, 2009)).…”
unclassified